2011
DOI: 10.1186/1758-2946-3-51
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into pharmaceutically relevant mutagenicity data and the influence on Ames predictive potential

Abstract: BackgroundIn drug discovery, a positive Ames test for bacterial mutation presents a significant hurdle to advancing a drug to clinical trials. In a previous paper, we discussed success in predicting the genotoxicity of reagent-sized aryl-amines (ArNH2), a structure frequently found in marketed drugs and in drug discovery, using quantum mechanics calculations of the energy required to generate the DNA-reactive nitrenium intermediate (ArNH:+). In this paper we approach the question of what molecular descriptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 67 publications
2
51
0
Order By: Relevance
“…Furthermore, the predicted AMES toxicity of Epicatechin will lead to genotoxicity and mutagenicity [81], the predicted hERG II potassium channel inhibitory effect of Acacetin Bprolongs the QT interval in ECG that increases the risk for potentially fatal ventricular arrhythmias^ [82]; subsequently, such drugs will not be considered as drug-likeness candidate (Table 9).…”
Section: -D-alanine D-alanine Ligase Enzymementioning
confidence: 99%
“…Furthermore, the predicted AMES toxicity of Epicatechin will lead to genotoxicity and mutagenicity [81], the predicted hERG II potassium channel inhibitory effect of Acacetin Bprolongs the QT interval in ECG that increases the risk for potentially fatal ventricular arrhythmias^ [82]; subsequently, such drugs will not be considered as drug-likeness candidate (Table 9).…”
Section: -D-alanine D-alanine Ligase Enzymementioning
confidence: 99%
“…The nitrenium hypothesis is likely best suited to predict the mutagenicity for a series of congeneric compounds as pointed out above when we discussed Borosky's work (49). The usefulness of the nitrenium hypothesis to predict the Ames activity was demonstrated by yet another group at Novartis (59)(60). McCarren et al found the same two equations, Equation 8 and 9, to give the best discrimination between Ames positive and Ames negative compounds.…”
Section: (10)mentioning
confidence: 98%
“…McCarren et al identified that besides the nitrenium ion formation energy, the AM1 calculated HOMO energy shows a good separation between Ames positive and Ames negative compounds (59). The nitrenium natural charge and the anion formation energy lead to much lower separation between the Ames positive and Ames negative classes.…”
Section: (10)mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the questions that have been raised about their relevance to pesticide registration, Ames mutagenicity tests remain a major regulatory hurdle that must be passed early in agrochemical pesticide development. Although hundreds of thousands of these assays have been performed, the majority of the results obtained are not publicly available.…”
Section: Toxicity Predictionmentioning
confidence: 99%